O beijo [re]cancelado : o épico como procedimento de tensionamento da obra de Nelson Rodrigues - Miranda, João Claudio Petrillo (2024)
The present work aims to identify ways of using epic elements as a tensioning procedure in Nelson Rodrigues‘ dramaturgy based on the adaptation of one of his plays, O beijo no asfalto (1961). The study seeks to understand how Nelson Rodrigues' work can enable, through the use of the epic as a tensioning procedure, the redefinition of his work through the work of an actor, which permeates the creation of characters, staging and text. To this end, works carried out by the author are discussed, initially A falecida, with Companhia Teatrofídico, in 2018, O beijo [cancelado] (2023), in the Acting Internship of the Department of Dramatic Art (DAD) at UFRGS, and finally O beijo [re]cancelado (2024), a practical object of study resulting from all these surveys. In this research, to highlight the developments and reference the tensions found, within the actor's work and dramaturgy, some key authors for the research and theoretical basis are presented, such as the philosopher Roland Barthes, who brings the poetic concept of punctum, and researcher Renato Ferracini, who uses this medium as an element that is also used in the creation process. To draw parallels between the work developed here and the epic in Nelson Rodrigues, the works of Anatol Rosenfeld and Bertolt Brecht are references. To this end, the research methodology is proposed to be a mix between the case study, in which the knowledge obtained from the articulation of theoretical and practical work is contributed, and interviews with people who worked with Nelson Rodrigues' work at some point. moment of their trajectories, establishing a cut in order to encompass the desired objectives and understand the urgency of a detailed look at works from the past.